Mechanism of INSR clustering with insulin activation and resistance revealed by super-resolution imaging. Issue 20 (17th May 2022) - Li, Hongru; Zhang, Jinrui; Shi, Yan; Zhao, Guanfang; Xu, Haijiao; Cai, Mingjun; Gao, Jing; Wang, Hongda
Abstract : Insulin receptor functional stability is regulated by βII-spectrin, which plays an important role in insulin regulation of GLUT4 for glucose transport. Abstract : Insulin receptor (INSR) is a key protein in the INSR signaling pathway and plays a critical role in biological processes, especially in the regulation of glucose homeostasis. Many metabolic diseases are often accompanied by abnormal INSR signaling. However, the specific effector mechanisms regulating insulin resistance and the distribution patterns of INSR during cell membrane activation remain unclear. Here, we investigated the changes in the distribution of INSR during activation using super-resolution imaging. By observing the connection between INSR activation and its distribution, we found that insulin resistance inhibits its receptor clustering. More importantly, we found that INSR has a highly co-localized relationship with the skeletal protein βII-spectrin. Specific knockout of βII-spectrin inhibited the interaction of INSR with GLUT4 and affected the normal metabolism of glucose. Our work elucidates the effects of insulin activation and insulin resistance on INSR distribution and reveals a potential relationship between INSR and cytoskeleton at the single molecule level, which promotes a deeper understanding of the roles associated with insulin signaling and insulin resistance.